Designing intervention prototypes to improve infant and young child nutrition in Peru: a participatory design study protocol - Rebecca Pradeilles; Paula Griffiths; Michelle Holdsworth; Emily Rousham; Rossina G Pareja; Hilary M Creed-Kanashiro; Rosario Bartolini; Deysi Ortega-Roman; Nervo Verdezoto (BMJ Open)
Introduction Nutrition during the complementary feeding period (6–23 months) is critical to ensure optimal growth and reduce the risk of diet-related disease across the life course. Strategies to reduce multiple forms of malnutrition (stunting, overweight/obesity and anaemia) in infants and young children (IYC) are a key priority in low-income and middle-income countries, including Peru. This study aims to co-design and develop prototypes for interventions to address the multiple forms of malnutrition in IYC in urban Peru, using a participatory design approach.Methods and analysis The study will be based within peri-urban communities in two areas of Peru (Lima and Huánuco city). Following the identification of key nutritional challenges for IYC aged 6–23 months through formative research (phase I), we will conduct a series of workshops bringing together healthcare professionals from government health centres and caregivers of IYC aged 6–23 months. Workshops (on idea generation; creating future scenarios; storyboarding and early implementation and feedback) will take place in parallel in the two study areas. Through these workshops, we will engage with community participants to explore, experiment, co-design and iteratively validate new design ideas to address the challenges around IYC complementary feeding from phase I. Workshop outputs and transcripts will be analysed qualitatively using affinity diagramming and thematic analyses. The intervention prototypes will be evaluated qualitatively and piloted with the participating communities.Ethics and dissemination Ethical approval for this study was obtained from the Ethical Review Committee of the Instituto de Investigación Nutricional (IIN) Peru (388-2019/CIEI-IIN), Loughborough University (C19-87) and confirmed by Cardiff University. Findings of the participatory design process will be disseminated through a deliberative workshop in Lima, Peru with national and regional government stakeholders, as well as participants and researchers involved in the design process. Further dissemination will take place through policy briefs, conferences and academic publications.